Central Nervous System Toxicity Following the Administration of Levobupivacaine for Lumbar Plexus Block: A Report of Two Cases. Issue 2 (1st March 2003) - Breslin, Dara S.; Martin, Gavin; MacLeod, David B.; D'Ercole, Francine; Grant, Stuart A.
Abstract : Background and Objectives: Central nervous system and cardiac toxicity following the administration of local anesthetics is a recognized complication of regional anesthesia. Levobupivacaine, the pure S(-) enantiomer of bupivacaine, was developed to improve the cardiac safety profile of bupivacaine. We describe 2 cases of grand mal seizures following accidental intravascular injection of levobupivacaine. Case Report: Two patients presenting for elective orthopedic surgery of the lower limb underwent blockade of the lumbar plexus via the posterior approach. Immediately after the administration of levobupivacaine 0.5% with epinephrine 2.5 μ g/mL, the patients developed grand mal seizures, despite negative aspiration for blood and no clinical signs of intravenous epinephrine administration. The seizures were successfully treated with sodium thiopental in addition to succinylcholine in 1 patient. Neither patient developed signs of cardiovascular toxicity. Both patients were treated preoperatively with β-adrenergic antagonist medications, which may have masked the cardiovascular signs of the unintentional intravascular administration of levobupivacaine with epinephrine. Conclusions: Although levobupivacaine may have a safer cardiac toxicity profile than racemic bupivacaine, if adequate amounts of levobupivacaine reach the circulation, it will result in convulsions. Plasma concentrations sufficient to result in central nervous system toxicity did not produce manifestations of cardiac toxicity in these 2 patients.